Perancangan Robot Maze Solving Berbasis Arduino - Doni, Rahmad; Fahlevi, Muhammad Reza; Syahrin, Elvin (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The maze solving robot is the development of the line follower robot. Where the robot can trace a path that has an intersection, in tracing a maze, apart from finding a way out / finish, it will be more efficient if the robot can find a shorter path through the maze. From the maze samples made, the robot can explore a maze and find the shortest path. When the mapping process is carried out, the robot traces 12 path codes; after the path simplification process is carried out, the robot can shorten the path it takes to 6.